2017
DOI: 10.1016/j.acalib.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Accuracy of Bibliographical References Generated for Medical Citation Styles by EndNote, Mendeley, RefWorks and Zotero

Abstract: Bibliographical references to online and printed articles, books, contributions to edited books and web resources generated by EndNote, Mendeley, RefWorks and Zotero were compared with manually written references according to the citation instructions in 15 biomedical journals and the NLM citation style. The fewest mistakes were detected in references generated by Zotero for 11 journals and the NLM style, while the second fewest number of mistakes was found in Mendeley. The largest number of mistakes for 9 jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 26 publications
0
21
0
13
Order By: Relevance
“…Tramullas, Sánchez-Casabón and Garrido-Picaso (2015) noted that papers that included PDF management features in their comparisons started appearing around 2010. Several studies have also focused on quality of citations generated by reference management software (Brahmi & Gall, 2006;Fitzgibbons & Meert, 2010;Gilmour & Cobus-Kuo, 2011;Homol, 2014;Kratochvíl, 2017) but there are fewer studies on the use of reference management software by particular user groups.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tramullas, Sánchez-Casabón and Garrido-Picaso (2015) noted that papers that included PDF management features in their comparisons started appearing around 2010. Several studies have also focused on quality of citations generated by reference management software (Brahmi & Gall, 2006;Fitzgibbons & Meert, 2010;Gilmour & Cobus-Kuo, 2011;Homol, 2014;Kratochvíl, 2017) but there are fewer studies on the use of reference management software by particular user groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the main challenges identified by students in this study related to problems with generating correct citations and the difficulty in learning how to use the programs. These citation problems may be due to inaccurate output styles (Brahmi & Gall, 2006;Kratochvíl, 2017). Brahmi and Gall (2006) found that many of the citation errors in EndNote and RefWorks could be fixed by editing the output style.…”
Section: Challengesmentioning
confidence: 99%
“…Bagian kedua terdiri atas empat pertanyaan tertutup yang berkaitan dengan penilaian responden terhadap hal yang berkaitan dengan pelaksanaan pelatihan. (Courraud, 2014;Kratochvíl, 2017;Ray & Ramesh, 2017).…”
Section: Metodeunclassified
“…Sebaliknya, kelemahan End-Note diantaranya: Tingkat kesalahan dalam pengutipan nya lebih tinggi daripada zotero (Kratochvíl, 2017), dan search interface yang terdapat dalam EndNote terkadang tidak memberikan dokumen jurnal yang sesuai dengan keyword yang dituliskan (Fitzgibbons & Meert, 2010).…”
Section: Hasil Dan Pembahasanunclassified
“…La perspectiva sobre la problemática que experimentan los profesores en la comunicación científica es una situación cultural. Aunque si esta barrera se supera, la siguiente situación corresponde a la capacidad en la preparación de manuscritos, los cuales van desde la creación de ideas innovadoras y la estructura armónica de los textos hasta la búsqueda de alternativas de publicación (Kratochvíl 2017).…”
Section: Condición De Los Profesores En Su Adaptación a Los Formatos unclassified